Rational antibiotics use-related behavior patterns and associates: a cross-sectional survey among Chinese community adults - Dan WANG; Meng HAN; Lixia DUAN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore behavior patterns of rational antibiotics use and their impact factors among community residents for providing evidence to implement targeted-promotion of rational antibiotics use in China. MethodsUsing convenient sampling and a questionnaire self-designed according to capacity-opportunity-motivation-behaviors (COM-B) model，we conducted an online survey among 481 adults ( ≥ 18 years) from three urban communities in Hubei, Hebei and Jiangsu province during 5 - 19 of September, 2020. Latent class analysis was used to identify the public antibiotic use behavior patterns and multi-nominal logistic regression model was adopted in analyses on influencing factors of different behavior patterns. ResultsAmong the 413 participants with valid responses, three behavioral patterns of antibiotic use were identified, namely "irrational antibiotics use", "antibiotic self-medication", "relatively rational antibiotics use", and the proportion of the participants for the three groups was 27.12% 27.12% and 45.76%, respectively. The results of logistic regression analysis showed that in comparison with the participants assessed as having "relatively rational antibiotics use ", higher scores of medication-related skills (odds ratio [OR] = 0.663, P = 0.037), social influence (OR = 0.475, P = 0.002), resource and environment (OR = 0.643, P = 0.042), self-capability beliefs (OR = 0.589, P = 0.034), and intentions (OR = 0.504, P = 0.004) were protective factors against irrational antibiotics use but with a family member suffering from chronic diseases (OR = 1.895, P = 0.039) was a promoting factor for irrational antibiotics use for the participants assessed as having "irrational antibiotics use"; for the participants having "antibiotic self-medication", higher scores of social influence (OR = 0.565, P = 0.004), behavioral reinforcement (OR = 0.486, P = 0.013) and knowledge (OR = 0.379, P = 0.019) were significant protective factors against irrational antibiotics use. ConclusionIn this survey, three different antibiotic use behavior patterns were identified among community adults in China; lack of relevant skills, adverse social influence, inadequate environment resources, insufficient belief in ability, strong intention to use antibiotics, and with family member suffering from chronic diseases are risk factors for irrational antibiotics use in the adults.